Bovine tuberculosis source attribution using decision tree analysis: breakdown investigations in Italy (2022–2023) - Tamba, Marco; Galletti, Giorgio; Loda, Daniela; Salvato, Sara; De Nardi, Marco; Boniotti, Maria Beatrice (Frontiers in Veterinary Science, 2025)
In this study, we present an overview of 348 Bovine Tuberculosis (bTB) breakdowns reported in Italy between January 2022 and December 2023, and declared resolved between January 2022 and February 2025. The main objective of this study is to investigate the most probable sources of these bTB breakdowns using decision tree analysis, and to compare the findings with conclusions drawn by official veterinarians. Most of the studied breakdowns (332; 95.4%) involved cattle herds only, 11 (3.1%) involved water buffalo herds only, and five (1.4%) involved multiple species. bTB was primarily detected in beef herds (82.8%), while mixed and dairy herds represented 10.3 and 6.9% of the breakdowns, respectively. In half of the breakdowns, the number of reactors was four or fewer. We also collected genotype data for 268 Mycobacterium tuberculosis complex isolates from 191 (54.9%) different breakdowns. M. bovis (255 isolates; 95.1%) came from 180 (94.2%) breakdowns, showing wide genetic variability. M. caprae (13 isolates; 4.9%) came from 11 (5.8%) breakdowns. Finally, we investigated the probable sources of infection, considering the five most frequently proposed sources of bTB breakdowns: (i) residual infection; (ii) introduction of infected cattle from other herds; (iii) sharing of pastures with infected herds; (iv) contiguous spread from infected neighboring herds; and (v) interaction with wildlife reservoirs. For each source, a decision tree was developed, and a likelihood of infection was assigned to each end node of the trees. The analysis identified residual infection (11.2%) as the most frequent source of bTB breakdowns, followed by sharing of pastures (10.9%) and interaction with wildlife (7.2%). The introduction of infected cattle and contiguous spread from infected neighboring herds were identified as less relevant sources. These tools allowed us to identify a likely source of infection in about 26% of cases. The results of our study, although based on scientific criteria, showed poor agreement with the conclusions of the veterinary officers who conducted the breakdown investigations in the field. In our opinion, these tools, when added to the “classic” investigation methodologies, should improve their effectiveness in identifying sources of infection in bTB breakdowns in Italy, supporting the eradication of this zoonotic disease.